2018
DOI: 10.31580/apss.v2i3.344
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning Processes as predecessor of Organizational Effectiveness : Conditional Process Analysis

Abstract: Organizational learning processes are considered to be on of the vital predecures for creation of new products and services or bringing newness in existing ones (Khoshkhoo and Nadalipour, 2016). Operationalization of organizational learning has been one of the well dicussed area of many researchers but still operationalization of organizational leaning processes need attention of researchers (Argote, 2012). This research has enhanced the dimesnions of organizational learning processes by incorporating cogntive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a more recent study, Gillani and Kiani (2018) assessed organizational learning processes as predecessors of organizational effectiveness. The results of their study revealed that organizational learning process has a significant effect on organizational effectiveness through mediation of organizational innovation and moderation of work attitude of employees.…”
Section: Constructs and Processes Associated With Organizational Learmentioning
confidence: 99%
“…In a more recent study, Gillani and Kiani (2018) assessed organizational learning processes as predecessors of organizational effectiveness. The results of their study revealed that organizational learning process has a significant effect on organizational effectiveness through mediation of organizational innovation and moderation of work attitude of employees.…”
Section: Constructs and Processes Associated With Organizational Learmentioning
confidence: 99%